2020
DOI: 10.1002/nop2.550
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among family nurses in Poland: A questionnaire‐based study

Abstract: Professional work occupies a significant part in our life. It is satisfaction of financial and material needs, but also has social and psychological dimension. Job satisfaction has a direct impact on the individual's life, self-esteem and fulfilment. The concept of satisfaction, despite many attempts to standardize it, is still a difficult category to standardize. The first research results on job satisfaction were published in the 1930s (Hersey, 1932; Hoppock, 1935; Mayo, 1933). The reason for interest in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…These results in the same line with the study of Kalinowska, and Marcinowicz (16) showed that the staff nurses were moderately satisfied with their job. Also the study supported with Chien and Yick (3) who showed that the majority of staff nurses had an overall moderate level of satisfaction with their work.…”
Section: Discussionsupporting
confidence: 89%
“…These results in the same line with the study of Kalinowska, and Marcinowicz (16) showed that the staff nurses were moderately satisfied with their job. Also the study supported with Chien and Yick (3) who showed that the majority of staff nurses had an overall moderate level of satisfaction with their work.…”
Section: Discussionsupporting
confidence: 89%
“…These findings reinforce that many nursing professionals are working in working conditions that are not favorable to their health and that can lead them to dissatisfaction and consequently to the desire to change their profession, as observed in this study. Other studies describe professional dissatisfaction at high levels, with remuneration being an influential factor in professionals' quality of life, but it does not overlap with other stressors discussed in other studies (40)(41)(42) .…”
Section: Discussionmentioning
confidence: 90%
“…Esses achados reforçam que muitos profissionais de enfermagem estão trabalhando em condições de trabalho que não são favoráveis à sua saúde e que podem levá-los à insatisfaçãoe consequentemente ao desejo de mudar de profissão, como foi constatado neste estudo. Outrosestudos descrevem a insatisfação profissional em níveis elevados, sendo a remuneração um fator influente na qualidade de vida do profissional, porém não se sobrepõe a outros fatores estressores discutidos em outras pesquisas (40)(41)(42) .…”
Section: Discussionunclassified